Argyreia elliptica (Roth ex Roem. & Schult.) Choisy: A New Distributional Record for North and North-East India - Balkrishna, Acharya; Joshi, Bhasker; Srivastava, Anupam; Shankar, Rama; Mishra, Rajesh Kumar; Kumar, Amit (Indian Forester, 2024)
No Abstract.